Towards stronger paving blocks: The combined effects of cement–sand mix proportion and geometry on compressive strength - Julianto Lubis (Societa: Journal of Society and Change, 2026)
The compressive strength of paving blocks is influenced not only by mix proportion but also by geometric configuration, yet comparative studies addressing both factors using local materials remain limited. This study aimed to analyze the effects of cement–sand mix proportion and paving block geometry on compressive strength. A quantitative experimental approach was employed through laboratory testing of two paving block types (Paving Stone and Eskoosix) using four cement–sand mix proportions (1:2, 1:3, 1:4, and 1:5) following SNI 03-1745-2000. The results showed that the 1:2 mix proportion produced the highest compressive strength, reaching 403.13 kg/cm² for Paving Stone and 401.84 kg/cm² for Eskoosix, whereas the 1:5 mix proportion yielded the lowest values. In addition, Paving Stone consistently exhibited higher compressive strength than Eskoosix. The findings demonstrate that mix proportion is the primary factor governing compressive strength, while paving block geometry contributes to optimizing stress distribution, providing a practical reference for developing local-material-based paving blocks. Abstrak Perbedaan kuat tekan paving block tidak hanya dipengaruhi oleh komposisi campuran, tetapi juga oleh bentuk geometrinya, sementara kajian yang membandingkan kedua faktor tersebut pada paving block berbasis material lokal masih terbatas. Penelitian ini bertujuan menganalisis pengaruh variasi komposisi semen-pasir dan bentuk paving block terhadap kuat tekan. Penelitian menggunakan metode kuantitatif dengan pendekatan eksperimental melalui pengujian laboratorium terhadap dua tipe paving block (Paving Stone dan Eskoosix) dengan empat variasi campuran semen-pasir (1:2, 1:3, 1:4, dan 1:5) sesuai SNI 03-1745-2000. Hasil penelitian menunjukkan bahwa campuran 1:2 menghasilkan kuat tekan tertinggi, yaitu 403,13 kg/cm² pada tipe Paving Stone dan 401,84 kg/cm² pada tipe Eskoosix, sedangkan campuran 1:5 menghasilkan nilai terendah. Selain itu, tipe Paving Stone secara konsisten menunjukkan kuat tekan yang lebih tinggi dibandingkan tipe Eskoosix. Penelitian ini menegaskan bahwa komposisi campuran merupakan faktor dominan, sedangkan geometri paving block berperan dalam mengoptimalkan distribusi tegangan sehingga dapat menjadi acuan pengembangan paving block berbasis material lokal.